Effect of Different Derivatives of Shikonin from Lithospermum erythrorhizon Against the Pathogenic Dental Bacteria - Li, Ming-yu; Xu, Zhu-ting; Zhu, Cai-lian; Wang, Jun (Current Pharmaceutical Analysis, 2012)
The objective of this study is to isolate and identify antibacterial compounds from Lithospermum erythrorhizon (L. erythrorhizon). Initially, the extracts of 44 different Traditional Chinese Medicines (TCM) were screened for their antimicrobial sensitivity by using broth micro-dilution methods on 96-microwell plate towards four different species of oral bacteria, which includes Fusobacterium nucleatum, Porphyromonas gingivalis, Streptococcus mutans and Lactobacillus acidophilus. Among the 44 TCMs, the extracts from L. erythrorhizon have proved to be most effective against these bacteria and were taken up for further study. Further, the purification of compounds from the selected L. erythrorhizon was performed by silica gel column chromatography. The compounds of L. erythrorhizon were evaluated for their efficacy by using antimicrobial sensitivity tests. Of all the extracts of L. erythrorhizon, 80% ethanol extract of it, has shown the best antibacterial effects. The elucidation of the structure of the isolated compounds was performed by NMR spectroscopy. Antibacterial effects of the compounds (Acetylshikonin, shikonin, deoxyshikonin, β-sitosterol, and β, β- dimethylacrylshikonin) obtained from the extract, showed that acetylshikonin has the best antibacterial effects. Our study concludes that acetylshikonin of L. erythrorhizon could be a potential antimicrobial agent for the treatment of oral diseases.
Keywords: antimicrobial agents